Le Monde comme il va, vision de Babouc - Voltaire, 1694-1778 (Salt Lake City, UT : Project Gutenberg, 2004)
"Le Monde comme il va, vision de Babouc" by Voltaire is a philosophical tale published in 1748. The angel Ituriel sends Babouc, a Scythian, to observe the city of Persepolis and determine whether its corruption warrants divine punishment. As Babouc journeys through the city, he encounters contradictions at every turn$1 (Bsplendor and squalor, virtue and vice, wisdom and foolishness. His observations swing between disgust and admiration, challenging his judgments about what makes a society worthy of survival or destruction. (This is an automatically generated summary.)s
Wikipedia page about this book: https://fr.wikipedia.org/wiki/Le_Monde_comme_il_va
Release date is 2004-02-01
This eBook was produced by Carlo Traverso
Keywords: French fiction -- 18th century